Conflicts of life and death - O'Donohoe, B (1986)
﻿ This thesis proposes that Sartre's plays are predominantly life-affirming, and their violence can be explained in terms of their central theme: conflict between life and death. Extensive reference is made throughout to Sartre's non-dramatic writings. This theme occurs on the literal and metaphorical planes: characters struggle for life, commit violent acts, and emerge 'existentially alive', or 'existentially dead'. Sartre's theories of life and death are summarised, and three examples of existential death considered. The theme is then analysed in each play under the headings 'Myth and Situation', 'Act and Agent'. Bariona's colonised people eventually escape from existential death, having contemplated martyrdom, when Bariona is influenced by the life-enhancing philosophy of Balthazar, and the experience of the Nativity. Argos, also, is suffused with death: 'Philèbe''s need to 'feel' his existence impels him to act definitively, punishing the regicides, and coming to existential life in his true identity as Oreste. In Huis clos, Sartre explores the deadness of lives led in moral cowardice, and the implicit message is, ironically, life-affirming. Morts sans sépulture propounds an argument for life which prevails, despite the hollow victory of the 'miliciens'. La Putain illustrates a triumph for the mortifying force of essentialist ethics. A seemingly comparable triumph of death in Les Mains sales is, in fact, a defeat for Hugo and an implicit victory for the life-advocate, Hoederer. Goetz exemplifies existential life perfectly, reaching it via every kind of moribund moral idealism. Kean burlesques Oreste's experience, escaping his vacuity through metaphorical suicide, and individualistically asserting his right to life. Nekrassov's hero parodies Goetz's odyssey, finally opting for life in the imaginary realm. Les Séquestrés depicts the triumph of death as man is crushed by the march of History. Les Troyennes, however, still advocates hope. Why did Sartre quit the theatre? Did the 'hero', through whom life is affirmed, become impossible?